2017
DOI: 10.18632/oncotarget.19192
|View full text |Cite
|
Sign up to set email alerts
|

A tyrosine kinase-STAT5-miR21-PDCD4 regulatory axis in chronic and acute myeloid leukemia cells

Abstract: MicroRNAs (miRNAs) are regulators of several key patho-physiological processes, including cell cycle and apoptosis. Using microarray-based miRNA profiling in K562 cells, a model of chronic myeloid leukemia (CML), we found that the oncoprotein BCR-ABL1 regulates the expression of miR-21, an “onco-microRNA”, found to be overexpressed in several cancers. This effect relies on the presence of two STAT binding sites on the promoter of miR-21, and on the phosphorylation status of STAT5, a transcription factor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…2b). This was consistent with previous studies that have shown increased expression of HBZ in imatinibtreated cells 14,15 . Differentially expressed genes (DEGs) between the two transition states were also identified ( Supplementary Fig.…”
supporting
confidence: 94%
“…2b). This was consistent with previous studies that have shown increased expression of HBZ in imatinibtreated cells 14,15 . Differentially expressed genes (DEGs) between the two transition states were also identified ( Supplementary Fig.…”
supporting
confidence: 94%
“…Internal tandem duplication of receptor-type tyrosine-protein kinase FLT3 (FLT3) and partial tandem duplication of lysine methyltransferase 2A (MLL) are the most common mutations in AML (with frequencies of 30-45% and 5-10%, respectively, in CN-AML), and are associated with poor therapeutic outcomes (20,21). Specifically, lymphoid-specific helicase and enhancer of polycomb homolog 1 were associated with epigenetic regulation in hematopoiesis (22), ring finger protein, LIM domain interacting (RLIM) was associated with the ubiquitylation of AML1-ETO and protein PML-retinoic acid receptor α (23), and programmed cell death 4 was associated with related signaling pathway (24) in myeloid leukemia. MLL (KMT2A) was associated with fusions and acute leukemia (25), and La ribonucleoprotein domain family member 4B (26), jumonji domain containing 1C (JMJD1C) (27) and SYNCRIP (28) (35).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unsupervised clustering was performed with scRNA-seq data from patient B using the SC3 pipeline (version 1.12.0) (19). The functions of DGEs were determined through a literature review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)…”
Section: Gene Fusion Predictionmentioning
confidence: 99%
“…Espadinha et al used microarray-based miRNA expression profiling in CML model K562 cells and found that oncoprotein BCR-ABL1 is dependent on the presence of two STAT binding sites on the miR-21 promoter and the phosphorylation of STAT5 to regulate the expression of miR-21 [43]. Wang et al found that emodin showed anti-tumor activity in vivo and in vitro by inactivating PTEN/PI3KAKT and deleting BCR-ABL to induce apoptosis [44].…”
Section: Discussionmentioning
confidence: 99%